DAMPAK PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN KADER POSYANDU TENTANG PEDOMAN UMUM GIZI SEIMBANG (PUGS) DI PONDOK BETUNG PONDOK AREN - Djafar, Meylina (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
The general guidelines of Balanced Nutrition (PUGS) need to be socialized to all walk Indonesian society in order to improve the understanding and the ability to consume food, healthy behaviors based on 4 pillars principles, namely: (1) variety of food consumption, (2) behaviors of clean living, physical activity, (3) and (4) maintain a normal body weight. Posyandu cadre has a very important role in supporting the achievement of behavior level that supports the health status improvement of the whole family. The purpose of this research was to determine the relationship between the knowledge and attitude of posyandu cadre acts of PUGS in the community. This research is a case study conducted at Posyandu in Pondok Betung Village RW 01 Pondok Aren District for 3 days in June 2013 with a sample of 56 people and using questionnaires. The results showed that: (1) there is no relationship between the level of education with action cadre of Posyandu PUGS, (2) there is no relation between the age and the action of posyandu cadre PUGS, (3) there was no connection between the job action cadre of posyandu about PUGS. (4) there is a link between knowledge and action cadre of posyandu about PUGS, (5) there is no relationship between the attitude of posyandu cadre with the action of PGUS.